SOSIALISASI IMPLEMENTASI ENERGI TERBARUKAN PADA KELOMPOK TANI DESA JABALSARI, KABUPATEN TULUNGAGUNG - Wakidah, Riska Nur; Haq, Siti Zaenab Nurul; Kristanti, Bella Arum; Damayanti, Annisa Maulidia (Universitas Mataram, 2024)
Jabalsari Village is one of the villages in Tulungagung district where the majority of the people make their living as farmers. Most of the agricultural system in Jabalsari Village still uses conventional methods. Apart from the method used, the energy source used in agricultural equipment still uses fossil fuels. Continuous use of fossil energy can disrupt the environmental ecosystem and will eventually run out. So, this Community Service activity aims to introduce renewable energy as an energy source for agricultural equipment. The method of implementing this activity is socialization. Socialization was carried out by providing explanations about renewable energy and its implementation. The activity began with an explanation from the PkM resource person and continued with a question and answer session between the lecturer and members of the Jabalsari village farmer group. The people of Jabalsari village who have participated in the activity have a better understanding of renewable energy and its implementation. Through this activity, it is hoped that farmers in Jabalsari village will understand the implementation of renewable energy in the agricultural sector and be able to put it into practice.